Differences In The Level Of Psychological Distress In 3rd Trimester Pregnant Women Who Followed Prenatal Yoga And Didi Not Follow Prenatal Yoga At Pratama Anugrah Clinic Surabaya - Delia Fellati Maharani; Endyka Erye Frety; Euvanggelia (Universitas STRADA Indonesia, 2024)
Background: Psychological distress is associated with the third trimester of pregnancy, where there is an increase in the level of psychological distress facing the birth period and prenatal yoga is one stress release that can be used. The aim of the research to analyze the differences of levels of psychological distress in third trimester pregnant women who participated in prenatal yoga and who did not participate in prenatal yoga. Method: used an observational study design with a cross sectional approach. The research instrument use questionnaire that is distributed directly using paper. Research data was analyzed using the Independent Sample T-Test. Results:Analysis of the Independent Sample T-Test test states that there is a difference with the (p value) = 0.011. Conclusion: is a difference in the level of psychological distress in third trimester pregnant women who take part in prenatal yoga and those who do not take part in prenatal yoga